Generation of an Elliptical Zeroth-Order Bessel Beam with a Deformable Annular Slit - Guaña, Dominic (Archīum Ateneo, 2020)
This dissertation investigates the generation of elliptical Bessel beams through the use of deformable annular slits. The manuscript is divided into three parts: the first discusses slit fabrications, followed by the computational investigations, and finally, the experimental methods.